1980
DOI: 10.1002/app.1980.070250713
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization from the vapor phase. I. Poly(p‐phenyleneterephthalamide) gas barrier coatings

Abstract: SynopsisAn atmospheric-pressure, vapor-phase polymerization technique was used to deposit thin (1-10 pm) poly(p-phenyleneterephthalamide) coatings onto polyester film and other sheet substrates. A minimum deposition temperature of 17OOC was found to be critical. When substrate temperatures were below 17OoC, coatings were loosely adhered, powdery, and of low molecular weight; above 17OoC, coherent, well-adhered, high molecular weight coatings were obtained. These vapor-deposited coatings exhibited exceptionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Vapor Phase Polymerization PPTA can be formed by vapor phase polymerization at temperatures above 2508C (31). The polymer produced appears to have a high degree of branching, which makes the spinning of fibers with high strength more difficult.…”
Section: Laboratory Synthesis Solution Polymerizationmentioning
confidence: 99%
“…Vapor Phase Polymerization PPTA can be formed by vapor phase polymerization at temperatures above 2508C (31). The polymer produced appears to have a high degree of branching, which makes the spinning of fibers with high strength more difficult.…”
Section: Laboratory Synthesis Solution Polymerizationmentioning
confidence: 99%
“…It generally increases with increasing permeant concentration, temperature, pressure difference, and decreases with increasing crystallinity, permeant size, chain stiffness, cohesive energy density, etc 17–20. High barrier polymers have been developed, for example, the poly(vinylidiene)chloride (PVDC),21 poly(ethylene vinyl) alcohols (EVOH),22 polyamides,23 sulfonated HDPE,24 poly( p ‐phenyleneterephthalamise) (PPTA),25 and liquid crystalline polymers (LCPs)26–28 which suffer from their high price 29. Developments of gas barrier thin film on polymer substrates started in 1959 with aluminum metallization technique 30.…”
Section: Introductionmentioning
confidence: 99%
“…In 1980, Ikeda et al 5 first reported the technique of in situ vapor deposition of monomers and polymerization ͑via step growth, not plasma͒ in vapor phase or vapor deposition polymerization ͑VDP͒. They reported the formation of Kevlar or poly͑p-phenyleneterephthalamide͒ via the simultaneous vapor deposition of p-phenylene diamine and terephthaloyl chloride, and since then, several others have performed VDPs using many different monomer combinations.…”
mentioning
confidence: 99%